2002
DOI: 10.1093/clinchem/48.9.1571
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin, Flavin Mononucleotide, and Flavin Adenine Dinucleotide in Human Plasma and Erythrocytes at Baseline and after Low-Dose Riboflavin Supplementation

Abstract: Background: Vitamin B2 exists in blood as riboflavin and its cofactors, flavin mononucleotide (FMN) and FAD. The erythrocyte glutathione reductase activation coefficient (EGRAC) has traditionally been used to assess vitamin B2 status in humans. We investigated the relationships of EGRAC and plasma and erythrocyte concentrations of riboflavin, FMN, and FAD in elderly volunteers and their responses to riboflavin administration. Methods: EGRAC and plasma and erythrocyte concentrations of riboflavin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 28 publications
4
79
2
1
Order By: Relevance
“…However, the results of Hustad et al (2002) are in contrast with an observational study (Vasilaki et al, 2010) that reported, in 119 healthy subjects, a positive correlation between plasma FMN and FAD, and between plasma free riboflavin and plasma FAD or FMN (r = 0.5, 0.49 and 0.55, respectively; p < 0.001).…”
Section: Plasma Riboflavin Fad and Fmn Concentrationcontrasting
confidence: 79%
See 2 more Smart Citations
“…However, the results of Hustad et al (2002) are in contrast with an observational study (Vasilaki et al, 2010) that reported, in 119 healthy subjects, a positive correlation between plasma FMN and FAD, and between plasma free riboflavin and plasma FAD or FMN (r = 0.5, 0.49 and 0.55, respectively; p < 0.001).…”
Section: Plasma Riboflavin Fad and Fmn Concentrationcontrasting
confidence: 79%
“…Erythrocyte FMN (but not FAD) was positively correlated with erythrocyte free riboflavin (p < 0.001). However, contrary to Hustad et al (2002), erythrocyte FAD was weakly but significantly correlated with plasma FAD (r = 0.21, p < 0.05).…”
Section: Erythrocyte Riboflavin Fad Fmn Concentrationmentioning
confidence: 67%
See 1 more Smart Citation
“…In Table 2, key reasons for categorizing studies in moderate or high risk of bias are described. No controlled diet during intervention period (Madigan, Tracey et al 1998;McKinley, McNulty et al 2002;Tavares, Moreira et al 2009) No controlled diet during intervention period (Hustad, McKinley et al 2002;McNulty, Dowey et al 2006) biomarkers could not be measured for all study subjects for unknown reasons (Hustad, McKinley et al 2002) Clear presentation of study results are missing, main results presented in figures with percentage of change (McNulty, Dowey et al 2006) Prospective cohort Risk of bias in exposure assessment; high correlation between micronutrients in the diet (Hankinson, Stampfer et al 1992;Badart-Smook, van Houwelingen et al 1997;Brzozowska, Kaluza et al 2008;de Vogel, Dindore et al 2008;Kabat, Miller et al 2008;Maruti, Ulrich et al 2009;Uccella, Mariani et al 2011;Bassett, Hodge et al 2012;Bassett, Severi et al 2012;Zschabitz, Cheng et al 2013) Risk of bias in exposure assessment; high correlation between micronutrients in the diet (Fortes, Forastiere et al 2000;Dallosso, McGrother et al 2004) Small population size (Fortes, Forastiere et al 2000) Information on exposure and outcome assessment is limited (Liu, Hazra et al 2013) No appropriate reporting of/adjustment for confounding (Dallosso, McGrother et al 2004) Dietary intake and status were measured during pregnancy and not in lactation phase (Shaw 1993;Ortega, Quintas et al 1999) Case-cohort Risk of bias in exposure assessment; high correlation between micronutrients in the diet (de Vogel, Dindore et al 2008) Nested casecontrol Risk of bias in exposure assessment; high correlation between micronutrients in the diet (Jacques, Chylack et al 2001;…”
Section: Quality and Risk Of Bias Assessmentmentioning
confidence: 99%
“…Hustad et al studied riboflavin status after riboflavin supplementation in 46 elderly men and women (mean age about 69 years) selected for a suboptimal riboflavin status (EGRAC ≥ 1.20) from a larger population of 124 subjects (Hustad, McKinley et al 2002). This randomised controlled trial was of high risk of bias.…”
Section: Riboflavin Restriction or Supplementation And Biomarkers Of mentioning
confidence: 99%